Efektivitas Video Learning Materi Pencemaran Lingkungan Pada Mata Kuliah Ilmu Lingkungan Prodi Pendidikan Biologi FKIP UAD : (The Effectiveness of Video Learning of Environmental Pollution Materials in the Environmental Science Course of Biology Education Study Program, FKIP UAD) - Yahya Hanafi; Destri Ratna Ma’rifah; Arief Abdillah Nurusman; Galuh Alif Fahmi Rizki (BIODIK, 2021)
Biology Education Study Program students, FKIP UAD have a learning style that tends to be auditive-visual. Based on these student characteristics, it is necessary to select appropriate and appropriate learning media to retain the information provided as much as possible. Therefore it is required to use learning media to accommodate student learning styles, namely by using video learning media. This study aims to determine the effectiveness of using video learning material on environmental pollution in the Environmental Science course. Video learning of environmental pollution material used includes water, soil, and air pollution. The research design is one-group pretest-postest design. The research was conduct at the Biology Education Study Program FKIP UAD in March-August 2018. The population in this study were all students of the Biology Education Study Program FKIP UAD semester VI academic year 2017-2018,  125 people (class A, B, C). Data collection techniques using observation and tests. The instruments used were the observation sheet and pre-post test. Data analysis includes prerequisite tests and hypothesis testing using the gain score and t-test. The results of the gain score for classes A, B, and C were obtained in the moderate category (0.3 ≤ g ≥0.7), meaning that there was an increase in learning outcomes using video learning. The t-test shows a significant difference between the pretest and post-test. The video learning of environmental pollution material is effectively used in the learning process of Environmental Science. Abstrak. Mahasiswa Prodi Pendidikan Biologi FKIP UAD memiliki gaya belajar yang cenderung auditif-visual. Berdasarkan karakteristik mahasiswa tersebut diperlukan pemilihan media pembelajaran yang tepat dan sesuai. Oleh karena itu perlu menggunakan media pembelajaran yang dapat mengakomodir gaya belajar mahasiswa, yaitu dengan penggunaan media pembelajaran video. Penelitian ini bertujuan untuk mengetahui efektivitas penggunaan video learning materi pencemaran lingkungan pada mata kuliah Ilmu Lingkungan. Video learning materi pencemaran lingkungan yang digunakan meliputi materi pencemaran air, tanah, dan udara. Desain penelitian yaitu  one-group pretest-postest design. Penelitian dilaksanakan di Program Studi Pendidikan Biologi FKIP UAD pada bulan Maret–Agustus 2018. Sampel penelitian ini mahasiswa semester VI prodi Pendidikan Biologi FKIP UAD tahun akademik 2017-2018, berjumlah 125 orang (kelas A,B,C). Teknik pengumpulan data menggunakan teknik observasi, dan tes. Instrumen yang digunakan yaitu lembar observasi dan soal. Teknik analisis data deskriptif kuantitatif, analisis data meliputi uji prasyarat dan uji hipotesis menggunakan gain score dan uji t. Hasil gain score untuk kelas A, B, dan C diperoleh kategori sedang (0,3 ≤ g ≥0,7), artinya terdapat peningkatan hasil belajar dengan menggunakan video learning. Hasil uji t menunjukkan terdapat perbedaan signifikan antara pretes dan postes sehingga video learning materi pencemaran lingkungan efektif digunakan dalam proses pembelajaran Ilmu Lingkungan.